Advances in Prostate Cancer Immunotherapy: Current Options and Emerging Novel Approaches - Nasser S Alanazi; Mohammed H Alrafiah (Annals of Urologic Oncology, 2024)
Prostate cancer (PCa) is a significant malignancy in men, contributing considerably to the rise in male mortality rates worldwide. Men diagnosed with PCa may have either localized or advanced stages of the disease. Globally, it ranks as the second most common and fifth most aggressive cancer type in males. The likelihood of developing prostate cancer in a man’s lifetime is approximately one in seven. Epidemiological research has linked various environmental and genetic factors to the abnormal growth of prostate cells, which leads to the formation of cancerous cells. Men experiencing a recurrence of prostate cancer or presenting with metastasis typically undergo androgen deprivation therapy (ADT), along with salvage radiotherapy and chemotherapy. While current treatment methods are more effective when used in combination, prostate cancer remains incurable. Research efforts are focused on exploring alternative treatments, including traditional medicine, nanotechnology applications, and gene therapy, to address drug resistance and mitigate the side effects associated with existing treatments. This article provides an overview the current treatment methods, and ongoing research into new treatment alternatives.